Longitudinal profiling of circulating miRNA during cardiac allograft rejection: a proof‐of‐concept study. (13th March 2021) - Kennel, Peter J.; Yahi, Alexandre; Naka, Yoshifumi; Mancini, Donna M.; Marboe, Charles C.; Max, Klaas; Akat, Kemal; Tuschl, Thomas; Vasilescu, Elena‐Rodica M.; Zorn, Emmanuel; Tatonetti, Nicholas P.; Schulze, Paul Christian
Abstract: Aims: Allograft rejection following heart transplantation (HTx) is a serious complication even in the era of modern immunosuppressive regimens and causes up to a third of early deaths after HTx. Allograft rejection is mediated by a cascade of immune mechanisms leading to acute cellular rejection (ACR) and/or antibody‐mediated rejection (AMR). The gold standard for monitoring allograft rejection is invasive endomyocardial biopsy that exposes patients to complications. Little is known about the potential of circulating miRNAs as biomarkers to detect cardiac allograft rejection. We here present a systematic analysis of circulating miRNAs as biomarkers and predictors for allograft rejection after HTx using next‐generation small RNA sequencing. Methods and results: We used next‐generation small RNA sequencing to investigate circulating miRNAs among HTx recipients (10 healthy controls, 10 heart failure patients, 13 ACR, and 10 AMR). MiRNA profiling was performed at different time points before, during, and after resolution of the rejection episode. We found three miRNAs with significantly increased serum levels in patients with biopsy‐proven cardiac rejection when compared with patients without rejection: hsa‐miR‐139‐5p, hsa‐miR‐151a‐5p, and hsa‐miR‐186‐5p. We identified miRNAs that may serve as potential predictors for the subsequent development of ACR: hsa‐miR‐29c‐3p (ACR) and hsa‐miR‐486‐5p (AMR). Overall, hsa‐miR‐486‐5p was most strongly associated with acute rejection episodes. Conclusions: Monitoring cardiac allograft rejection using circulating miRNAs might represent an alternative strategy to invasive endomyocardial biopsy.